A flow formulation for the optimum communication spanning Ttee - Fernández, Elena; Luna-Mota, Carlos; Hildenbrandt, Achim; Reinelt, Gerhard; Wiesberg, Stefan (Electronic notes in discrete mathematics, 2013)
In this paper we address the Optimum Communication Spanning Tree Problem. We present a formulation that uses three index variables and we propose several families of inequalities, which can be used to reinforce the formulation. Preliminary computational experiments are very promising.
Gesehen am 12.03.2021